CASE STUDY VIOLATION OF ACADEMIC ETHICS AND ITS IMPACT ON STUDENT ACHIEVEMENT - Helmi Amelia Putri Ritonga; Dihan Al Farisi; Dwi Irmawati; Amanda Amelia Sitepu; Ajib Syah Buyung (CV. Asy Persada Quality, 2025)
Academic ethics violations among university students are a serious issue that threatens the quality of higher education and the integrity of graduates. Various forms of misconduct such as plagiarism, cheating, and data manipulation are still commonly found in students' academic activities. This study aims to analyze the forms, causes, and impacts of academic ethics violations on student performance. The method used is a descriptive qualitative approach through literature review and analysis of case studies from various academic journals. The findings show that academic misconduct reflects a lack of moral understanding and has direct consequences, including decreased academic performance, reduced motivation to learn, and a damaged student reputation. In contrast, students who uphold academic integrity tend to achieve better results and demonstrate stronger character. Therefore, the systematic and contextual cultivation of academic ethics is essential to shaping students who are both high-achieving and morally groundedissue that can threaten the quality of higher education and the integrity of graduates. of ethics reflect weak moral understanding, and have a direct impact on declining academic achievement, loss of learning motivation and damage to students' reputations. On the other hand, students who uphold the value of integrity tend to have better achievements and stronger characters. The instillation of academic ethics in a real way plays a role in forming students with character and achievement